Powassan Encephalitis in New Brunswick - Fitch, William M. (1990)
A case Powassan encephalitis was diagnosed in a 76-year-old man who had viral encephalitis. The patient had been staying at a cottage in Upper Rexton, north of Moncton, New Brunswick. No history of tick bite was elicited. Seven months after onset, the patient is much improved in his cognitive and physical functioning, but has minor memory impairment. This is the 11th case of Powassan encephalitis to be recognized in Canada and the first from New Brunswick.